2017
DOI: 10.4085/1062-6050-52.11.26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Sport Concussion Assessment Tool 3 (SCAT3) Tandem-Gait Test in High School Athletes

Abstract: Our findings suggest that the tandem-gait test had a high false-positive rate in high school athletes. Given that more than 75% of healthy participants failed the tandem-gait test, the 14-second cutoff appears to have limited clinical utility in the adolescent population. Functional movement deficits after concussion need to be accounted for, but the 14-second cutoff for the SCAT3 tandem-gait test does not appear to be an ideal way to assess these deficits in high school athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…In addition, the mean single-task test completion time among our cohort of participants was approximately 14 seconds. Although 14 seconds was the recommended pass/fail criterion in the SCAT3, 29 our results align with those of Santo et al, 23 who observed that this threshold resulted in a high false-positive rate and that this time should not be used for all adolescent athletes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the mean single-task test completion time among our cohort of participants was approximately 14 seconds. Although 14 seconds was the recommended pass/fail criterion in the SCAT3, 29 our results align with those of Santo et al, 23 who observed that this threshold resulted in a high false-positive rate and that this time should not be used for all adolescent athletes.…”
Section: Discussionsupporting
confidence: 88%
“…The primary outcome variable was the time required to complete the test, averaged across 3 trials completed in each condition and was selected based on previous research. 9,10,[20][21][22][23] This outcome is consistent with the SCAT3 test, whereas the SCAT5 uses a pass/fail criterion. No participants failed a trial (defined as an overt separation of the heel and toe, stepping off the tape, or touching the test administrator), so using a pass/fail criterion as a primary outcome measure would not have yielded meaningful results among our sample.…”
Section: Testing Timelinesupporting
confidence: 72%
“…e corresponding mainstream algorithms include pose estimation algorithm, linear model, compound pose estimation regression algorithm, and other algorithms [31][32][33].…”
Section: Related Research: Research Status Of Motion Training System ...mentioning
confidence: 99%
“…2 The Center for Disease Control and Prevention estimates that up to 3.8 million SRCs occur each year in the United States, and 21% to 27% of injuries sustained in high school sports are SRCs. 3,4 Concussion may result in impaired performance in neurological [5][6][7] or physical/physiological domains. 8,9 It is estimated that at least 20% of SRCs are undiagnosed or unreported, with SRCs accounting for up to 50% of adolescent concussions in Canada.…”
Section: Introductionmentioning
confidence: 99%